Internal savings and lending scheme for ensuring sustainable agricultural development in rural areas: A case of Chimanimani District. - Huchu, Xavier T. (Midlands State University, 2017)
Internal Savings and Lending Schemes has become very important in global poverty reduction. The popular hypothesis is that by enabling rural poor households access to loans and savings enables poor households begin micro enterprises which would help them improve their income generation and escape poverty eventually. The chief research objective of this dissertation was to examine the role played by internal savings and lending schemes in rural areas, as a way of ensuring sustainable Agricultural development. The study is an investigational case of Chimanimani District where participants in internal savings and lending schemes was studied acquiring a rich pooled data for analysis. The results indicate a positive and significant impact of internal savings and lending schemes on household agriculture, productivity, durable assets acquisition and food security. On the other hand the research emphasizes that there is need to expand information dissemination channel, use of holistic and coordinated strategy as part of recommendations.